2018
DOI: 10.1002/fut.21971
|View full text |Cite
|
Sign up to set email alerts
|

Indian equity options: Smile, risk premiums, and efficiency

Abstract: We study the pricing of equity options in India which is one of the world's largest options markets. Our findings are supportive of market efficiency: A parsimonious smile‐adjusted Black model fits option prices well, and the implied volatility (IV) has incremental predictive power for future volatility. However, the risk premium embedded in IV for Single Stock Options appears to be higher than in other markets. The study suggests that even a very liquid market with substantial participation of global institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 10 publications
(40 citation statements)
references
References 47 publications
(80 reference statements)
3
37
0
Order By: Relevance
“…Christensen and Prabhala ( 1998 ) showed that implied volatility outperforms historical volatility in forecasting future volatility. Since then, other researchers have confirmed the evidence across markets (Poon & Granger, 2003 ), including for India (Jain et al, 2019 ; Panda et al, 2008 ).…”
Section: Methodsmentioning
confidence: 83%
See 4 more Smart Citations
“…Christensen and Prabhala ( 1998 ) showed that implied volatility outperforms historical volatility in forecasting future volatility. Since then, other researchers have confirmed the evidence across markets (Poon & Granger, 2003 ), including for India (Jain et al, 2019 ; Panda et al, 2008 ).…”
Section: Methodsmentioning
confidence: 83%
“…The options price reflects the uncertainty over the option's remaining life and not the uncertainty observed in the past. It is well established in the literature that globally implied volatility from the options market leads the realized volatility (Christensen & Prabhala, 1998 , Poon & Granger, 2003 ), and this has been verified in India as well (Jain et al, 2019 ).…”
Section: Literature Review and Research Questionsmentioning
confidence: 89%
See 3 more Smart Citations